Chronic inflammatory bowel diseases: the course and treatment methods in Russian Federation (Results of multicenter population-based one-stage observational study) - L. . Khalif; M. V. Shapina; A. O. Golovenko; Ye. A. Belousova; Ye. Yu. Chashkova; A. V. Lakhin; O. V. Knyazev; A. Yu. Baranovsky; N. N. Nikolayeva; A. V. Tkachev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To evaluate the prevalence of clinical manifestations and variants of progression for ulcerative colitis (UC) and Crohn’s disease (CD) in population of the Russian Federation. Material and methods. The present investigation was designed as population-based one-stage observational study. The clinical data, treatment methods, laboratory tests results and the rate of adverse effects for patients with inflammatory bowel diseases (IBD) from 8 gastroenterological centers were obtained. Severity grade was estimated by a doctor. Encoding of concurrent therapy, complications and systemic manifestations was carried out according to MedDRA. Results. Original study included overall 1000 patients (667 UC patients, 333 CD patients). Most of the study patients were diagnosed to have chronic relapsing (53.1% for UC; 45.0% for CD) or chronic persistent (32.8% with UC; 39.65 with CD) course of disease, mild attack was revealed in 51.3% of UC patients and 52.3% of CD patients, moderate attack in 46.6 and 47.3% respectively. Systemic manifestations and complications of the disease were found in 33.5% of patients. At the moment of enrollments to the study patients received maintenance therapy, most frequently - by the drugs containing 5-aminosalicylic acid (72.0% for UC, 59.5% for CD) and immunosuppressors (28.0% for UC, 42.6% for CD); biological agents are prescribed rarely (11.75% for UC, 20.4% for CD). Previous surgical intervention was present in the past history of 43.8% CD patients and 5.7% - UC patients. The median (range) hospital admissions was 1 (1-10) in those with UC and 1 (1-24) in those with CD. Conclusions. High complication rate, previous surgical intervention and changes of therapeutic tactics demonstrates that treatment approaches to this cohort of IBD patients in the Russian Federation are not optimal enough.